An institutional study of cesarean delivery on maternal request - Sri, A. Shanti; Khanam, Nazia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cesarean delivery on maternal request refers to a primary cesarean delivery performed because the mother requests this method of delivery in the absence of a standard medical/obstetrical indication for avoiding vaginal birth. The aim of the study was to find out the reasons behind, and the incidence of women preferring Cesarean section in the absence of obstetric and medical indications. Methods: This was a prospective study among women who came for delivery at Princess Esra Hospital, Deccan College of Medical Sciences, Hyderabad, over a period of one year from 1st April 2015 to 31st March 2016. All women who underwent Cesarean delivery for maternal request were included in this study. Results: The total number of deliveries during the study period of one year was 2574. There were 1346 (52.29%) vaginal deliveries and 1228 (47.7%) cesarean deliveries. Among 1228 Cesarean deliveries, 87 (7.08%) had maternal request as their indication. Majority of them were in the age group of more than 35 years. Multigravidae opted for Cesarean delivery more than primigravidae (59 multigravidae vs 28 primigravidae). Among the various reasons for women requesting delivery cesarean were tocophobia, refusal of trial of labor after Cesarean section (TOLAC), concurrent sterilization, prolonged infertility and treatment conception, afraid of neonatal outcome (previous adverse neonatal outcome) and astrological concerns. Conclusions: Many of the women opted for Cesarean delivery in our study for preventable reasons like painless labor and concurrent sterilization which would have been easily avoided by prior counseling starting from antenatal period and by providing labor analgesia. Patient education and personal involvement of the treating obstetrician in counseling the patient and emotional support during labor can reduce Cesarean delivery for maternal request.